Implications of Private- Sector Tools and Methods in Public Administration: A Review of The Most Crucial Reforms of Public Administration - Panagiota I. XANTHOPOULOU; Ioannis ANTONIADIS; Sotiria I. TRIANTARI (Communications of International Proceedings, 2022)
Public sector worldwide faces increasingly pressing challenges. In recent years, it is commonly accepted that adopting practices and tools from the private sector, such as “strategic thinking”, “customer focus”, “performance measurement”, “new technologies” and “continuous improvement” is the best way to address many of the problems in public sector’s management. The current paper presents some of the most important and contemporary tools and practices of the private sector that were introduced in public administration especially from the New Public Management reform until today. The current study followed the integrative or critical review approach which aims to evaluate, analyze, and synthesize the literature on a study issue in a way that encourages the emergence of new theoretical frameworks and viewpoints. The importance of the study lies in two points, first the research approach is not common on the administration literature and secondly it adds more information from the current literature, and this could help researchers and policymakers to identify the key best practices that will increase the quality of public services. Findings showed that while there are many reforms in the Greek public administration, some of them failed to reach their final aim due to issues such as corruption, mismanagement, and maladministration. However, the Greek public administration significantly introduced a strategic way of thinking and managing the organisations.
Keywords: Public sector reforms; Performance Measurement; Strategic Management; Digitalization